Comparison of the isolated direct photon cross sections in p(p)over-bar collisions at root s=1.8 TeV and root s=0.63 TeV - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2002)
We have measured the cross sections d2σ/d P Tdη) for production of isolated direct photons in pp̄ collisions at two different center-of-mass energies, 1.8 TeV and 0.63 TeV, using the Collider Detector at Fermilab. The normalization of both data sets agrees with the predictions of quantum chromodynamics for a photon transverse momentum (PT) of 25 GeV/c, but the shapes versus photon PT do not. These shape differences lead to a significant disagreement in the ratio of cross sections in the scaling variable xT(≡ 2PT/√s). This disagreement in the xT ratio is difficult to explain with conventional theoretical uncertainties such as scale dependence and parton distribution parametrizations. © 2002 The American Physical Society.